DIFFICULTY OF SOLVING PROBLEMS STORY SOLVED MATERIAL STUDENTS OF CLASS 5 UPT SDN 1 BITTUANG (LITERATURE REVIEW STUDY) - Paulina Feronika Arruan (Publikasi dan UKI Press UKI Toraja., 2023)
This study aims to describe students' mistakes in solving word problems in the aspects of understanding the problem, planning problem solving, and carrying out problem solving. In this study, researchers used a literature study. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. Based on research on students' difficulties in working on math word problems on fractional material, it can be concluded that (1) Difficulties in solving word problems include: difficulty reading questions, difficulty understanding problems, difficulty transforming problems, difficulty calculating processes, and difficulty writing conclusions about the final answer. Students experience the most difficulties in the calculation process, especially in determining the denominator of fractions with different denominators. Errors in the calculation process were made 204 times by the research subjects on all the questions tested. (2) There are three factors that cause students to make mistakes, namely due to difficulty understanding the problem, not understanding fractional concepts and operations, and causes of errors due to forgetfulness, carelessness, and haste. (3) Solutions that can be made to minimize students' mistakes in working on story problems are to increase the practice of working on story problems, make story questions in a more communicative language, apply cooperative learning in teaching story problems, and provide explanations using concrete props